Bioactivity of sesquiterpenes: compounds that protect from alcohol-induced gastric mucosal lesions and oxidative damage - Repetto, Marisa G. (2010)
Sesquiterpene lactones of the guaianolide and eudermanolide types are considered of interest because they have an effect in the regulation and prevention of oxidative damage and inflammation-mediated biological damage. Dehydroleucodine, a natural sesquiterpene isolated from Artemisia douglasiana Besser, and ilicic aldehyde, a semi-synthetic sesquiterpene lactones, showed in vivo protection in ethanol-induced gastric mucosa damage. This action was determined by in situ gastric mucosa chemiluminescence and by tissue antioxidant content.